Damage mechanics of solder/IMC interface fracture in pb-free solder interconnects - Tamin, Mohd. Nasir (2009)
This study addresses the mechanics of the relatively brittle solder/intermetallic (IMC) interface fracture process using damage mechanics concept. The damage state, ¿ of a material point in the solder/IMC interface, is expressed in terms of orthogonal traction components in a quadratic failure criterion of a cohesive zone model. The model is then employed in a finite element analysis of a solder ball shear push test. The simulated test specimen consists of reflowed SAC405 solder-on-OSP copper pad and orthotropic FR4 substrate. Unified inelastic strain constitutive model with optimized material parameters describes the strain rate-response of the SAC405 solder. The cohesive zone model parameter values are compiled from published experimental data on SAC405 solder ball pull tests and shear push tests. The predicted shear tool force-displacement curve compared well with published experimental data. The normal-to-shear traction ratio at the onset of interface fracture is 1.59 indicating significant induced bending effect due to shear tool clearance. Rapid interface crack propagation is predicted following the initiation of crack with the average crack speed up to 24.6 times the applied shear tool speed at 3000 mm/sec. The progressive boundary between damaged (¿<1.0) and fractured (¿=1.0) interface is interpreted as the interface crack front. The high stress concentration along the edge of the solder/IMC interface facilitates local crack initiation and dictates the shape of the dynamic crack front.